Quantifying the potential of morphological parameters for human dental identification: part 3—selecting the strongest skeletal identifiers in the mandible - Iliescu, Anca R.; Capitaneanu, Cezar V.; Hürter, Debora; Fieuws, Steffen; De Tobel, Jannick; Thevissen, Patrick W. (International journal of legal medicine, 2022)
The current study aimed to select the best mandibular morphological identifiers. One-hundred eighty-five panoramic radiographs were retrospectively collected, in which four landmarks were located on the mandible: the most superior point of the condyle right/left (CONR/L), of the coronoid right/left (CORR/L), of the mandibular lingula right/left (LINR/L), and the most mesial point of the mental foramen right/left (MMFR/L). Five linear measurements, 6 angles, and 10 ratios were measured bilaterally. Three groups of statistics were considered: (1) mean potential set; (2) inter-observer agreement quantified by intra-class correlation (ICC) and within-subject coefficient of variation (WSCV); and (3) Spearman correlation. Parameters were selected for a step-by-step cascade. In a univariate approach, the following parameters proved to have the best identifying capacity: ratio 3 right (between lines CONR — CORR and LINR — MMFR) with mean potential set 13%, ICC 0.90, and WSCV 4.8%; ratio 4 (between lines CONR/L — CORR/L and MMFR — MMFL) with mean potential set 13%, ICC 0.92, and WSCV 8.9%; and angle 4 left (between landmarks LINL, MMFL, and MMFR) with mean potential set of 18%, ICC 0.91, and WSCV 1.2%. The correlation coefficients ranged from 0.01 to 0.33. In a multivariate approach, the identifying capacity improved drastically, with all ratios combined as the strongest identifier (mean potential set 1.29%). In conclusion, a single ratio or a single angle already narrows down the set of potential matches, but the mean potential set remains relatively large. Combining all ratios drastically increases the certainty of the match.